2011
DOI: 10.3389/fpsyg.2011.00101
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Speech-Relevant Auditory Acuity in Absolute Pitch Possessors

Abstract: Absolute pitch (AP) is the ability to identify the frequency or musical name of a specific tone, or to identify a tone without comparing it with any objective reference tone. While AP has recently been shown to be associated with morphological changes and neurophysiological adaptations in the planum temporale, a cortical area in the brain involved in speech perception processes, no behavioral evidence of speech-relevant auditory acuity in any AP possessors has hitherto been reported. In order to seek such evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…In order to confirm the major findings of previous studies about unusual musical sensitivity of children with ASD, subsidiary data were collected after the completion of the above experiments from all the participants about AP, the ability to identify the frequency or musical name of a specific tone, or to identify a tone without comparing it with any objective reference tone (Masataka, 2011). The parents of the participants were also interviewed to ask about instances of extraordinary musical memory in their children, which has been reported to occur often in association with ASD (Kanner, 1943).…”
Section: Introductionmentioning
confidence: 92%
“…In order to confirm the major findings of previous studies about unusual musical sensitivity of children with ASD, subsidiary data were collected after the completion of the above experiments from all the participants about AP, the ability to identify the frequency or musical name of a specific tone, or to identify a tone without comparing it with any objective reference tone (Masataka, 2011). The parents of the participants were also interviewed to ask about instances of extraordinary musical memory in their children, which has been reported to occur often in association with ASD (Kanner, 1943).…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, the distribution of the age of first formal musical training in a large number of individuals with AP can be modeled with a gamma function with a mode at 4–6 years (Levitin and Zatorre, 2003 ). Training that begins after the age of 9 very rarely leads to AP, and there are no known cases of an adult successfully acquiring it (Brady, 1970 ; Ward and Burns, 1999 ; Levitin and Rogers, 2005 ). The appropriate type of input, i.e., training associating absolute pitches to labels, thus needs to be available before the end of the critical period for AP to develop.…”
Section: Introductionmentioning
confidence: 99%
“…From a behavioral perspective, evidence shows that pitch identification is more precise for iterated rippled noise, which provides temporal cues for pitch processing in the auditory pathway, than for narrow band noise, in which pitch information resides primarily on place cues ( Fujisaki and Kashino, 2005 ). Another study showed that musicians with high precision AP were more efficient in identifying speech syllables in an automated, bottom-up task than musicians with low performance in a pitch identification task ( Masataka, 2011 ). In a recent study, frequency resolution predicted performance at pitch labeling ( Reis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%